Proteomics reveals multiple effects of titanium dioxide and silver nanoparticles in the metabolism of turbot, Scophthalmus maximus. (December 2022) - Araújo, Mário J.; Sousa, Maria L.; Fonseca, Elza; Felpeto, Aldo Barreiro; Martins, José Carlos; Vázquez, María; Mallo, Natalia; Rodriguez-Lorenzo, Laura; Quarato, Monica; Pinheiro, Ivone; Turkina, Maria V.; López-Mayán, Juan José; et al.
Abstract: Titanium dioxide (TiO2 ) and silver (Ag) NPs are among the most used engineered inorganic nanoparticles (NPs); however, their potential effects to marine demersal fish species, are not fully understood. Therefore, this study aimed to assess the proteomic alterations induced by sub-lethal concentrations citrate-coated 25 nm ("P25") TiO2 or polyvinylpyrrolidone (PVP) coated 15 nm Ag NPs to turbot, Scophthalmus maximus . Juvenile fish were exposed to the NPs through daily feeding for 14 days. The tested concentrations were 0, 0.75 or 1.5 mg of each NPs per kg of fish per day. The determination of NPs, Titanium and Ag levels (sp-ICP-MS/ICP-MS) and histological alterations (Transmission Electron Microscopy) supported proteomic analysis performed in the liver and kidney. Proteomic sample preparation procedure (SP3) was followed by LC-MS/MS. Label-free MS quantification methods were employed to assess differences in protein expression. Functional analysis was performed using STRING web-tool. KEGG Gene Ontology suggested terms were discussed and potential biomarkers of exposure were proposed. Overall, data shows that liver accumulated more elements than kidney, presented more histological alterations (lipid droplets counts and size) and proteomic alterations. The Differentially Expressed Proteins (DEPs) were higher in Ag NPs trial. The functional analysis revealed that both NPs caused enrichment of proteins related to generic processes (metabolic pathways). Ag NPs also affected protein synthesis and nucleic acid transcription, among other processes. Proteins related to thyroid hormone transport ( Serpina7 ) and calcium ion binding ( FAT2 ) were suggested as biomarkers of TiO2 NPs in liver. For Ag NPs, in kidney (and at a lower degree in liver) proteins related with metabolic activity, metabolism of exogenous substances and oxidative stress (e.g.: NADH dehydrogenase and Cytochrome P450) were suggested as potential biomarkers. Data suggests adverse effects in turbot after medium/long-term exposures and the need for additional studies to validate specific biological applications of these NPs. Graphical abstract: Image 1 Highlights: TiO2 and Ag NPs induced histological and proteomic alterations, mainly in liver. Titanium and silver accumulated in turbot liver. TiO2 and Ag NPs affected energy/lipid metabolism. Ag NPs also altered ribosome and protein biosynthesis related processes and others. The proteomic study provided candidate biomarkers for NPs exposure.